A comparison of vitamin D and cathelicidin (LL-37) levels between patients with active TB and their healthy contacts in a high HIV prevalence setting: a prospective descriptive study. (16th August 2021) - Lungu, Patrick Saili; Kilembe, William; Lakhi, Shabir; Sukwa, Thomas; Njelesani, Evarist; Zumla, Alimuddin I; Mwaba, Peter
Abstract: Background: Studies from Asia and Europe indicate an association between vitamin D deficiency and susceptibility to TB. We performed an observational case-control study to determine vitamin D and cathelicidin (LL-37) levels and their association with active TB in newly diagnosed and microbiologically confirmed adult TB patients in Zambia, a high HIV prevalence setting. Methods: Both total vitamin D and LL-37 were measured using ELISA from serum and supernatant isolated from cultured whole blood that was stimulated with heat-killed Mycobacterium tuberculosis . Statistical analysis was performed using STATA statistical software version 12. Results: The median vitamin D in TB patients and healthy contacts was 28.7 (19.88–38.64) and 40.8 (31.2–49.44) ng/ml, respectively (p<0.001). The median LL-37 in TB patients compared with healthy contacts was 1.87 (2.74–8.93) and 6.73 (5.6–9.58) ng/ml, respectively (p=0.0149). Vitamin D correlation with LL-37 in healthy contacts was R 2 =0.7 (95% CI 0.566 to 0.944), p<0.0001. Normal vitamin D significantly predicted a healthy status (OR 4.06, p=0.002). Conclusions: Significantly lower levels of vitamin D and LL-37 are seen in adults with newly diagnosed active TB. Longitudinal studies across various geographical regions are required to accurately define the roles of vitamin D and LL-37 in preventive and TB treatment outcomes.